2014
DOI: 10.1002/bip.22572
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Aβ(25–35) fibrillation products with mitochondria: Effect of small‐molecule natural products

Abstract: The 25-35 fragment of the amyloid β (Aβ) peptide is a naturally occurring proteolytic by-product that retains the pathophysiology of its larger parent molecule, whose deposition has been shown to involve mitochondrial dysfunction. Hence, disruption of Aβ(25-35) aggregates could afford an effective remedial strategy for Alzheimer's disease (AD). In the present study, the effect of a number of selected small-molecule natural products (polyphenols: resveratrol, quercetin, biochanin A, and indoles: indole-3-acetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 84 publications
(600 reference statements)
1
18
0
Order By: Relevance
“…These results indicate that both polyphenols delay the onset of HEWL secondary structural conversion from a partially unfolded to ␤ structure, suggesting that they probably bind to amyloidogenic structures formed during early stages of fibrillation, and not to the monomers, in accord with earlier reports on studies involving a number of proteins/peptides [22,27,30,32,70]. Our observation that both polyphenols prolonged the lag time of HEWL fibrillation support the notion that the polyphenols interfere with the initial steps of HEWL amyloid formation (Table 1).…”
Section: Ra and Res Delay The Secondary Structure Transition Of Hewlsupporting
confidence: 90%
See 1 more Smart Citation
“…These results indicate that both polyphenols delay the onset of HEWL secondary structural conversion from a partially unfolded to ␤ structure, suggesting that they probably bind to amyloidogenic structures formed during early stages of fibrillation, and not to the monomers, in accord with earlier reports on studies involving a number of proteins/peptides [22,27,30,32,70]. Our observation that both polyphenols prolonged the lag time of HEWL fibrillation support the notion that the polyphenols interfere with the initial steps of HEWL amyloid formation (Table 1).…”
Section: Ra and Res Delay The Secondary Structure Transition Of Hewlsupporting
confidence: 90%
“…In this regard, numerous reports have demonstrated the effectiveness of some of the naturally occurring small molecules, and specially certain natural polyphenols, on prevention of protein aggregation and their associated cytotoxicity [24][25][26][27][28][29][30][31]. Recently, we too, have reported on inhibition of fibrillation as well as destabilization of preformed fibrils of A␤ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), using a range of small molecules, including polyphenols [32]. Based on structural similarities, a structure-function relationship study has suggested that the presence of at least two phenolic rings with two to six atom linkers, along with a minimum number of three OH groups on the aromatic rings, are essential for efficient polyphenol inhibition [22].…”
Section: Q2mentioning
confidence: 99%
“…The sections on the grids were post-stained for 2 min with 1% UA, and for 6 min with 1% lead citrate by the addition of single drops of the staining solution at room temperature. The sections were rinsed in deionized water, dried and finally observed using a H7650 electron microscope (Hitachi, Tokyo, Japan), as described in previous studies (Ghobeh et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Treatment of airway epithelial cells with quercetin during hMPV infection significantly reduced cellular oxidative damage, inflammatory mediator secretion, and viral replication, supporting the use of dietary antioxidants such as quercetin as an effective treatment approach for modulating hMPV-induced lung oxidative damage and inflammation (Komaravelli et al, 2015). Quercetin and other polyphenols, such as resveratrol, were used in a study to protect brain mitochondria from amyloid fragment fibrillogenesis (Ghobeh et al, 2014). Using rat hippocampal cultures, some authors have already been capable of delivering encapsulated quercetin, protecting neuronal cultures from oxidative stress, and hypothesizing its use against AD or other neurodegenerative disorders (Nday et al, 2015).…”
Section: Quercetinmentioning
confidence: 91%